Risk Communication Model Of Covid-19 Disaster Through Instagram And Twitter In Pemerintah Kabupaten Klaten - Elisabet Isyana Rahayu; Puji Lestari; Edwi Arief Sosiawan (Jurnal Komunikasi, 2023)
The third wave of the COVID-19 pandemic in Indonesia has affected various regions, including Klaten Regency, which is ranked third in the highest number of positive cases and second in the cumulative total in Central Java. Risk communication becomes crucial in reducing disaster risks due to COVID-19, and one effective avenue is through social media. The people of Klaten have started utilizing social media to receive information about COVID-19 and to provide feedback on the local government's handling of the pandemic. The objective of this research is to discover a risk communication model for COVID-19 disasters through social media in the Klaten Regency Government. This qualitative research employs interviews and social media analysis of the COVID-19 Task Force in Klaten Regency. The focus is on the risk communication model employed through social media by the Klaten Regency Government, with subjects being social media managers within the COVID-19 Task Force. The findings reveal a risk communication model that emphasizes enhancing social media management capabilities to mitigate the risks of COVID-19 in Klaten. This research contributes by introducing additional risk communication units to the existing COVID-19 risk communication model through social media and establishing Standard Operating Procedures (SOPs) for social media management in risk communication.